Pengaruh tingkat inflasi dan profitabilitas terhadap kualitas laba pada perusahaan - Elvika Nur, Elvika Nur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research has the aim of knowing the influence or impact caused by the inflation rate and profitability on the earnings quality of manufacturing companies, especially the consumer goods sector in 2018-2020. In this study, Return on Assets is an aspect in measuring profitability. The research method used is a quantitative research method where purposive sampling is the data collection technique. The population in this study are all manufacturing companies in the consumer goods sector published on the Indonesia Stock Exchange in 2018-2020. The total corporations that were decided to be carried out in this study were 28 corporations with a total sample of 84 samples. The hypothesis test is carried out by relying on the F test and T test. The results in this study are 1) Inflation has no effect on earnings quality and 2) Profitability affects earnings quality.